Prevalence of Schistosoma mansoni infection among children in Ethiopia: a systematic review and meta-analysis - Habtye Bisetegn (BMC, 2021)
Abstract Background Schistosomiasis is a neglected tropical disease caused by mainly Schistosoma mansoni and Schistosoma hematobium. The disease is very common in Africa including Ethiopia. Schistosoma mansoni is a major public health problem in Ethiopia especially among children. This review is aimed to indicate the prevalence of Schistosoma mansoni among children at the national and regional levels. Methods and material The PRISMA guidelines were followed. An electronic search of PubMed, Google Scholar, Web of Science, Scopus, MEDLINE, and Google search were carried out using key terms. Articles published from the proceeding of professional associations such as the Ethiopian medical laboratory association, the Ethiopian public health association, and annual national research conferences were also searched to find additional eligible studies. Data were extracted independently by two investigators, and cross-checked by a third reviewer. The quality of included studies was assessed using JBI quality assessment criteria. Data were extracted using Microsoft excel and finally analyzed using STATA version 12. The pooled prevalence was done using a random-effects model. Result Overall 49 studies involving 20,493 children (10,572 male and 9, 921 females) were included in this meta-analysis. The pooled prevalence of Schistosoma mansoni infection was 37.13% (95%CI:30.02–44.24). High heterogeneity was observed with I2 of 99.4%, P < 0.000. According to subgroup analysis, the pooled prevalence was high in the SNNPR (41.49%: 95%CI: 19.52–63.46) followed by the Amhara region (41.11%: 95%CI: 30.41–51.8), the Tigray region (31.40%: 95%CI:11.72–51.09), and the Oromia region (28.98%: 95%CI: 18.85–39.1). Year from 2011 to 2015 contributed to the highest prevalence of Schistosoma mansoni infection among children (46.31%: 95%:34.21–59.05). Conclusion This study revealed a 37.13% prevalence of Schistosoma mansoni infection among children. This is an alert to improve and implement appropriate control strategies such as mass drug administration in Ethiopia.